ATENCIÓN AL CLIENTE EN LA AGENCIA BANECUADOR - CABALLERO CASTELO, GABRIELA ISABEL (2018)
The Bank Ecuador agency is a Financial Institution belonging to the public financial sector of the province of Los Ríos, Babahoyo canton located on Malecón 9 de Octubre and Eloy Alfaro, which since May 9 began in 2016, aimed at influencing socioeconomic development of the country and citizen welfare, currently develops financial products and services of its worst care groups such as: individual and family productive units, productive and associative units, small and medium-sized communal productive units, SMEs for production, and entrepreneurs, with a clear focus on social commitment and financial sustainability.